MPPT 알고리즘의 주기에 따른 발전 영향 분석 - 민준기(Joonki Min); 최원석(Wonseok Choi) (전기학회 논문지 P권, 67(4), 2018)
In this paper, we compared power generation characteristics of two MPPT algorithms, P & O and InC, applied to grid-connected solar inverters. The MPPT detects the voltage and current of the solar module string and transfers the power to the DC link. Since the grid is connected by the power conversion circuit, the grid connection control and the MPPT control influence each other. The power generation characteristics were analyzed by Psim simulation according to the MPPT cycle in the weak grid conditions.